Pengaruh latihan back-up terhadap kemampuan menyundul bola - Kuswoyo, Dilli Dwi; Wasa, Carolus; Dongoran, M. Fadli (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2020)
The purpose of this study was to determine whether there is an effect of back-up training on the ability to head a ball in eighth grade male students of SMP YPK Merauke. The experimental method used for this study was a pre-test and post-test pattern. In the implementation of this research, the population was used, namely all students of class VIII SMP YPK Merauke for the 2019-2020 academic year. The total population of this study from each class, including; Class VIIIa consists of 28 students, VIIIb has 26 students, VIIIc has 28 students, and class VIIId has 25 students. The total population is 107 students. The number of samples in this study are; 6 students from class VIIIa, 5 students from class VIIIb, 6 students from class VIIIc, and from class VIIId there are 5 students. The total sample in this study was 22 students. The research instrument used a soccer heading test. The results of this study can be concluded that the back up exercise has an effect on the results of students' ball headers. It is proven that students who do back up exercises will produce good ball headers compared to students who head the ball without doing back up exercises.